A sign that tries to be a sign: About art production in cooperation between small and large beings - Jonvik, Merete (Nordic Journal of Art & Research, 2020)
This article departs from a participatory art project with a group of children and a professional artist, driven by the urge to explore invested attempts of horizontality in art production. The intention of the project was to explore whether equality and horizontality in art production is possible, and if so in what ways, and to investigate the outcomes of collaborative art production consisting of asymmetric relations. With the use of participant observation, interviews and photo documentation, both the article and the artwork are analysed. An exploration of equality and horizontality shows that the attempts ended precisely as attempts, rather than actual horizontality. Departing from this, the article discusses quality assessment of both process and results in participatory art projects. Experiences from our specific project indicate a mutual dependence between aesthetic and social aspects in quality assessments, thus questioning the separation of aesthetic and social aspects, with reference to Claire Bishop, Grant Kester and David Bell.